Is it Possible to Use Rolling Methods to Improve Textures on Fe-Mn-Si Shape Memory Alloys? - Druker, Ana Velia (2017)
No uniform rolling deformation produces shear strains that give rise to textural and microstructural heterogeneities in processed metals and alloys. In this work, the authors investigate Fe-30Mn-4Si shape memory alloy sheets rolled in different conditions at 600°C, in order to determine the process giving rise to the best structure and the strongest (100)<110> shear texture. This crystallographic orientation is the most favorable for the γ → ε martensitic transformation, which provides the shape memory effect in these alloys. In the current conditions, the authors find that unidirectional rolling produces a shear texture in sheet's surface layers. The authors compare the texture and microstructure from this process to those obtained from reverse rolling and single-roller drive rolling.